2015
DOI: 10.15359/ree.19-3.7
|View full text |Cite
|
Sign up to set email alerts
|

Agresiones en el noviazgo: Un estudio con adolescentes de Heredia (Costa Rica)

Abstract: Recibido 12 de setiembre de 2014 • Corregido 15 de junio de 2015 • Aceptado 31 de julio de 2015Gran parte del comportamiento agresivo humano se da en el contexto de una relación amorosa. El colectivo adolescente no es una excepción: las investigaciones señalan una notable prevalencia de este problema, evidenciándose la necesidad de profundizar en su estudio, especialmente en Iberoamérica, dada la escasez de trabajos al respecto. Este estudio tiene como objetivos fortalecer el conocimiento sobre el comportamien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
2
0
1
Order By: Relevance
“…From the analyzed data in this study, either as a consensus for both male and female participants or in the particular representations of the income variable; dating violence was not objectified only as physical, but also as verbal-emotional, relational, and sexual; which agrees with the classification proposed by Fernández-Fuertes et al (2015). Therefore, the youths in this study, with the aforementioned anchorages, demonstrated a comprehension of dating violence as a wide, complex, and multifaceted phenomenon.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…From the analyzed data in this study, either as a consensus for both male and female participants or in the particular representations of the income variable; dating violence was not objectified only as physical, but also as verbal-emotional, relational, and sexual; which agrees with the classification proposed by Fernández-Fuertes et al (2015). Therefore, the youths in this study, with the aforementioned anchorages, demonstrated a comprehension of dating violence as a wide, complex, and multifaceted phenomenon.…”
Section: Discussionsupporting
confidence: 80%
“…The final number for each variable that is fixed or based on an opinion means its association to: 1 = dating; or 2 = dating violence. When it was verified the predominance of the violence types, be it on the way to perpetrate or victimize these adolescents, these findings also corroborate the studies that were developed by Fernández-Fuertes et al (2015), as well as the one by Barreira et al (2014). So, it is ratified that, with the aforementioned data, dating and dating violence pervade the participants' daily lives; hence their characterization as SR-generating objects; which may produce senses and, consecutively, interfere with their behaviors.…”
Section: Discussionsupporting
confidence: 74%
“…To classify participants involved in one of three possible dyadic IPV perpetration types (male-only, female-only, and mutual), dyadic data about the problematic behavior are needed (experiences of perpetration and victimization). Because of the high prevalence of psychological IPV or coercive control (in comparison with physical violence) in university samples or youths documented elsewhere (e.g., Castro & Casique, 2010; Fernández-Fuertes, Orgaz-Baz, & De Lima-Silva, 2015; Sabina & Straus, 2008; Straus, 2008), controlling behavior is considered the focus for the dyadic categorization of perpetrators in this study. Male and female participants who perpetrated any form of control but did not experience any victimization from their partner are either classified as male-only and female-only, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, taking into account the types of violence, relational violence did show significant associations according to sex, in favour of boys. In the study of Fernández-Fuertes et al (2015) with a sample from educational centres in Costa Rica, boys also reported a slightly higher frequency than girls, but the authors pointed out that relational violence tends to be the least frequent among adolescents.…”
Section: Mcmillenmentioning
confidence: 97%